Pengaruh Pandemi COVID-19 Terhadap Kondisi Finansial Rumah Sakit - Amirsyani Ariestotama Ilyas; Theodore Isaac Molandro; Aaisyah Dia Palupi; Moona Fahira; Dian Purbani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The COVID-19 pandemic has put great pressure on hospitals, affecting clinical and non-clinical aspects such as patient care, resource management, and finances. This research analyzes the challenges faced by hospitals through crisis management theory and open systems, with a focus on financial pressures, staff shortages, and digital transformation. The purpose of this writing is to provide insight into hospital strategies in overcoming pandemic challenges, which is expected to improve hospital readiness in the future. Article search was conducted through international databases using the terms PICO and MeSH: P: